2019
DOI: 10.1002/cnma.201800550
|View full text |Cite
|
Sign up to set email alerts
|

Halide‐Induced Leaching of Pt Nanoparticles – Manipulation of Particle Size by Controlled Ostwald Ripening

Abstract: The synthesis of "surfactant-free" Pt nanoparticles (NPs) in alkaline ethylene glycol (EG), initially introduced in 2000, is of fundamental interest for the preparation of catalysts. Often a suspension of colloidal Pt NPs prepared by this method is stored and upon demand further processed to obtain supported catalysts such as PtÀC or PtÀAl 2 O 3 . In this study it is shown that in such colloidal suspensions in the presence of halides, e. g. from the metal precursor salt, leaching of Pt NPs takes place. Metal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 51 publications
(66 reference statements)
8
36
0
Order By: Relevance
“…The synthesis can be induced in various ways including using thermal sources (oil bath synthesis at ca. 160 °C), [31,33] micro‐wave, [34] UV‐light, [35,36] or even ambient conditions [37] . The as‐prepared NPs can be functionalized, e. g. by phase transfer reaction with lipophilic ligands (transfer into toluene) [31] .…”
Section: Surfactant‐free Colloidal Synthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis can be induced in various ways including using thermal sources (oil bath synthesis at ca. 160 °C), [31,33] micro‐wave, [34] UV‐light, [35,36] or even ambient conditions [37] . The as‐prepared NPs can be functionalized, e. g. by phase transfer reaction with lipophilic ligands (transfer into toluene) [31] .…”
Section: Surfactant‐free Colloidal Synthesesmentioning
confidence: 99%
“…The (long term) storage of colloids is a non‐trivial task. It was shown that the presence of residual halides in the synthesis could lead to NP leaching in the liquid phase [33] . Unprotected NPs are mainly functionalized with CO and HO − groups [47] .…”
Section: Preparation Of Supported Catalysts From Colloidsmentioning
confidence: 99%
“…However, a reported benefit of EG is the stability of its colloidal dispersions against flocculation. 29,30 Thus, to evaluate the colloidal stability, the as-prepared Ir NPs synthesized using MeOH and EtOH as solvent have been characterized by their Z-potential, see Figure 1. It is found that the colloidal Ir NP suspension prepared in MeOH exhibits a higher absolute Z-potential than the one prepared in EtOH.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, when re-dispersed in acetone, the suspension cannot be stored for a long time since Ir NPs seem to dissolve back very slowly to complex species forming a yellow solution, as previously observed for Pt NPs treated in the same manner. 30 In the next step, for each solvent (EtOH, MeOH, and EG) a series of Ir/C catalysts with different metal loadings, i.e., 10, 30, 50, 70 wt.% was prepared. We then determined the mean nanoparticle diameter of the different supported catalysts via SAXS.…”
Section: Solventmentioning
confidence: 99%
“…7 with fig. 8, which has been obtained from a "real" catalyst by the Arenz group, who have worked intensively on studying platinum nanoparticles in electrocatalysis [40][41][42]. Nanoparticles are favored as catalysts in fuel cells due to their high catalytic activity and high surface to volume ratio, allowing for very low amounts of the expensive material (we shall come back to this later).…”
mentioning
confidence: 99%